Association between small nucleolar RNA host gene expression and survival outcome of colorectal cancer patients: A meta-analysis based on PRISMA and bioinformatics analysis - Luo, Pei; Du, Jie; Li, Yinan; Ma, Jilong; Shi, Wenjun (Frontiers in Oncology, 2023)
Growing evidence shows that long non-coding RNA small nucleolar RNA host genes (lncRNA SNHGs) play an important role in the occurrence and development of colorectal cancer (CRC). However, no study has systematically explored the correlation between lncRNA SNHGs expression and prognosis of CRC. This study aimed to evaluate the prognostic value of lncRNA SNHGs in CRC patients using meta-analysis. Systematic searches were performed using PubMed (Medline), Embase, Web of science, the Cochrane Library, BioMed Central, Wanfang and China National Knowledge Internet computerized databases from inception to October 20, 2022. The quality of published papers was assessed in details. Pooled hazard ratios (HR) with 95% confidence interval (CI) were performed through direct and indirect collection of effect sizes. Pooled odds ratios (OR) with 95% CI were performed by collecting effect sizes within articles. Detailed downstream signaling pathways of lncRNA SNHGs were summarized in detail. A total of 25 publications with 2,342 patients were finally included to evaluate the association of lncRNA SNHGs with prognosis of CRC based on a systematic review and meta-analysis. Elevated lncRNA SNHGs expression was revealed in colorectal tumor tissues. High lncSNHG expression was associated with short overall survival in CRC patients (HR=1.635, 95% CI: 1.405–1.864, P<0.001). Additionally, increased lncRNA SNHGs expression showed positive correlation with later TNM stage (OR=1.635, 95% CI: 1.405–1.864, P<0.001), distant lymph node metastasis, distant metastasis, larger tumor diameter, and poor pathological grade. Begg's funnel plot test suggested that no significant heterogeneity was found. High expression of lncRNA SNHGs was revealed to be positively associated with poor CRC prognosis, and lncRNA SNHG could serve as a potential prognostic indicator and therapeutic target for CRC.